A Look Behind the Cancellation of 12 D-Con Brand Mouse and Rat Poison Products. (1st June 2013) - Unknown
Approximately 10, 000 children a year are accidentally exposed to mouse and rat baits, and rodenticide poisonings have been well documented in a wide variety of wildlife species, including some that are listed as threatened or endangered. In an effort to address these problems, the EPA set risk reduction standards for rodenticides to protect health and the environment better. In early 2013, the EPA moved to cancel 12 D-Con brand mouse and rat poison products that do not meet safety standards and cause unreasonable and unnecessary risks to children's health and the environment. The manufacturer of these 12 D-Con products, Reckitt Benckiser, Inc, refused to adopt the necessary risk mitigation measures for these products, which included adding protective bait stations to prevent children and pets from accessing the poison, and reformulating products that contain second-generation anti-coagulants. Without these important safety measures, the 12 D-Con products do not meet the statutory standard for registration in the Federal Insecticide, Fungicide, and Rodenticide Act (FIFRA).